2020
DOI: 10.3892/or.2020.7866
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyllin VII induces apoptosis and autophagy via mediating H2O2 levels and the JNK pathway in human osteosarcoma U2OS cells

Abstract: Polyphyllin VII, a compound extracted from the rhizomes of Paris polyphylla, has strong antitumor effects on various human tumor cell lines. However, few studies have reported the possible effect of Polyphyllin VII on human osteosarcoma (OS) cell lines. The present study revealed that Polyphyllin VII promoted OS cell apoptosis and inhibited cell proliferation via upregulating the expression of LC3II, Atg5, Atg7 and the Atg12-Atg5 complex. By contrast, treatment of OS cells with Polyphyllin VII downregulated At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that PPVII induces a variety of cell death modes, such as apoptosis, autophagy, and programmed necrosis, by activating c‐Jun N‐terminal kinase (JNK) signaling or inhibiting protein kinase B (Akt) signaling in a variety of tumor types (Ahmad, Gamallat, et al, 2021; X. Li et al, 2021; D. Pang et al, 2019; C. Zhang, Jia, Wang, et al, 2016; Zhang, et al, 2015). Both JNK and Akt are downstream kinases of TOPK, activated by TOPK phosphorylation but not limited to the regulation of TOPK (Song et al, 2019; Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that PPVII induces a variety of cell death modes, such as apoptosis, autophagy, and programmed necrosis, by activating c‐Jun N‐terminal kinase (JNK) signaling or inhibiting protein kinase B (Akt) signaling in a variety of tumor types (Ahmad, Gamallat, et al, 2021; X. Li et al, 2021; D. Pang et al, 2019; C. Zhang, Jia, Wang, et al, 2016; Zhang, et al, 2015). Both JNK and Akt are downstream kinases of TOPK, activated by TOPK phosphorylation but not limited to the regulation of TOPK (Song et al, 2019; Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphyllin VII, a steroidal saponin derived from Paris polyphylla Sm., possesses potent anticancer activity against various human cancer cell lines 13 , 14 . Previous studies have reported the inhibitory effects of polyphyllin VII on the proliferation and apoptosis induction of different types of cancer cells, including human lung cancer cells (A549 and NCI-H1299 cells), human oral cancer cells (SAS and OECM-1 cells), human liver cancer cells (HepG2 cells), human nasopharyngeal cancer cells (HONE-1 and NPC-039 cells) and human colorectal cancer cells (HCT-116 and HT-29 cells) 12 - 14 , 25 , 26 . In our study, we utilized our own established human lung cancer cell line CTC-TJH-01, which possesses metastatic capabilities, as well as the commercial lung cancer cell line H1975, to investigate the anticancer efficacy of polyphyllin VII.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that polyphyllin VII may induce autophagic cell death in HepG2 cells by inhibiting the PI3K/AKT/mTOR and activating the JNK pathways ( Zhang et al, 2016b ). Moreover, polyphyllin VII induced apoptosis and autophagy in human osteosarcoma U2OS cells by regulating the JNK pathway ( Li X. et al, 2021 ). Another study showed that polyphyllin VII promoted ROS production in HepG2 cells, leading to depolarization of mitochondrial membrane potential, upregulation of the Bax/BCL2 ratio and protein levels in cleaved forms of caspase-3, caspase-8, and caspase-9, and poly (ADP ribose) polymerase, which eventually led to apoptosis.…”
Section: Methods and Strategiesmentioning
confidence: 99%